Pengembangan E-Learning Mata Kuliah Profesi Keguruan Berbasis Moodle Untuk Model Blended Learning Di Universitas Islam Malang - Ganjar Setyo Widodo; Layli Hidayah (Universitas Kanjuruhan Malang, 2020)
Abstract: This study aims to develop E-Learning of “Mata Kuliah Profesi Keguruan” to be Blended Learning subjects. The method used in this research is the development research method using the ADDIE (Analysis-Design-Develop-Implement-Evaluate) model. Based on the results of the study, it can be concluded that e-learning of “Mata Kuliah Profesi Keguruan” has met the validity criteria with a value of 97.093% from expert validators. The product trial results with students obtained a positive response that is equal to 90% with the criteria of